تأثير البيئة القانونية على آلية فض منازعات المالية الإسلامية عن طريق التحكيم: الإمارات العربية المتحدة كنموذج) = The effect of the legal environment on the mechanism of resolving Islamic financial disputes through arbitration (United Arab Emirates as a model) - Laeba, Muhammad; Mohamed Zaki, Hesham Mahmoud (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
تناول البحث معالم البيئة القانونية التي تؤثر في صناعة التمويل الإسلامي، مع التركيز على الإطار القانوني الذي يخص آلية التحكيم الإسلامي والفرق بينه وبين التحكيم التقليدي وفق ما نص عليه قانون دولة الإمارات، وذلك من حيث الأساس القانوني والتنظيمي من قبل الدولة الذي يقوم بتنظيم عمل تلك الصناعة، والصعوبات والتحديات التي تعترض هذا النوع من التحكيم وإمكانية تجنبها، حيث إن من أهم دعائم البنية القانونية للصناعة المالية الإسلامية وجود جهات وهيئات متخصصة تعنى بالفصل في النزاعات المالية وبشكل خاص تلك التي تتفق مع أحكام الشريعة الإسلامية، وأن من المهم عند اختيار هيئة التحكيم في ذلك مراعاة البعد الفني لموضوع النزاع وكذلك البعد الشرعي والقانوني. كذلك طرق البحث إلى المرجعيات الشرعية المتعددة ومدى تأثير ذلك على فض المنازعات المتعلقة بالمالية الإسلامية، خصوصا بعد القرار الأخير الذي اتخذه البنك المركزي الإماراتي بإلزام كافة البنوك الإسلامية بما في ضمنها النوافذ الإسلامية داخل البنوك التقليدية وكذلك جميع شركات التمويل التي تقدم منتجا إسلاميا بتطبيق معايير هيئة المحاسبة والمراجعة للمؤسسات المالية الإسلامية أيوفي اعتبارا من سبتمبر لعام 2018. ويتوقع أن تتوصل تلك الدراسة التحليلية إلى عدة نتائج: من أهمها: أولا: أن توحيد المرجعيات الشرعية في المؤسسات المالية الإسلامية يسهم في زيادة ثقة المتعاملين معها. ثانيا: أن الصياغة غير الجيدة لاتفاق التحكيم تعد من أهم العقبات التي تواجه التحكيم الإسلامي، ولتجنب ذلك يكمن في اللجوء إلى التحكيم المؤسسي واختيار الصيغة النموذجية لاتفاق التحكيم. ثالثا: أن عدم تقنين أحكام الشريعة الإسلامية خصوصا في جانب المعاملات المالية وتقديمها دوليا على غرار أعراف التجارة الدولية أدى ذلك إلى تعطيل العمل بها أمام المحاكم الأجنبية. ********************************************************************************* The research dealt with the parameters of the legal environment that affects the Islamic finance industry, focusing on the legal framework for the Islamic arbitration mechanism and the difference between it and traditional arbitration in accordance with the law of the UAE, in terms of the legal and regulatory basis by the State which organizes The work of the Islamic finance industry, and the difficulties and challenges of this type of arbitration and the possibility of avoiding it, as one of the most important pillars of the legal structure of the Islamic financial industry is the existence of specialized bodies dealing with the settlement of financial disputes, especially those that comply with the provisions of the Islamic Shari'a, and it is important when choosing the arbitral tribunal to take into account the technical dimension of the subject matter of the dispute as well as the Shari'a dimension And legal.As well as the research dealt with the various Shari’a authorities and the impact on the dispute resolution related to Islamic finance.Especially after the recent decision by the UAE Central Bank to obligate all Islamic banks, including Islamic windows within conventional banks, as well as all Islamic finance companies that provide Islamic product to apply the standards of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) as of September 2018. This analytical study is expected to produce several results: first: he standardization of Shariah authorities in Islamic financial institutions contributes to increasing the confidence of clients. Second: The poor formulation of the arbitration agreement is one of the most important obstacles facing Islamic arbitration, and to avoid this lies in the use of institutional arbitration and the choice of model form of the arbitration agreement.Third: The non-codification of the provisions of Islamic law, especially in the aspect of financial transactions and international delivery in line with the norms of international trade has led to the disruption the application of Islamic law in foreign courts